# Yahoo Web Search

related to LHS

1. Sort by

1. ### im not sure which one but im certainly sure that its not B. help?

The answer is d - on the LHS you have 2 hydrogen atoms but on the left there's 4.

1 Answers · Science & Mathematics · 29/09/2018

2. ### Prove that (cos 2x - cos x) / (cos x - 1) = 2 cos x + 1 ?

LHS = (cos 2x - cos x) / (cos x - 1) = [ 2cos^2(x) - 1 - cos(x)]/[cos(x) - 1...

3 Answers · Science & Mathematics · 06/06/2018

3. ### What does it mean when A(dot)(B x C) = -A(dot)(B x C)?

LHS = -(LHS) ---> LHS + (LHS) = 0 2(LHS) = 0 or LHS = 0

5 Answers · Science & Mathematics · 02/05/2018

4. ### Prove that cosec y = cot y sec y?

...equation is not an identity, if that is what you mean. Let y = π/2. LHS = csc(y) = csc(π/2) = 1 RHS = cot(y)sec(y) = cot(π/2)sec(π/2) The...

6 Answers · Science & Mathematics · 21/04/2018

5. ### What's the smallest value of the natural number x(x ≠ 0), so that 280x is a perfect square?

...want that 2^3 * 5 * 7* x = n² For this, all powers on the LHS bust be multiples of 2 [why?]. So you need an extra 2 to make 2^4...

4 Answers · Science & Mathematics · 10/03/2018

6. ### 2 ≤ n, n ∈ N. prove ((n+1)/2)ⁿ > n!?

... does not hold because 1 ≠ 2 ≠ 3 ≠ etc. for n >= 2. LHS = [n(n+1)/2][1/n] = (n+1)/2 RHS = [n!]^(1/n) Therefore [(n+1...

2 Answers · Science & Mathematics · 15/02/2018

7. ### Prove 5^n + 6^n < 7^n is true for all natural numbers n > 2?

... is P(k + 1): 5^(k + 1) + 6^(k + 1) < 7^(k + 1) LHS = 5^(k + 1) + 6^(k + 1) = 5·5^k + 6·6^k = 5(5^k + 6^k) + 6^k RHS = 7...

4 Answers · Science & Mathematics · 05/03/2018

8. ### Use​ Newton s method to estimate all real solutions of the equation. Make your answers accurate to 6 decimal places.?

... to ensure no root is lost. (because sinx between -1 and 1, ditto for the LHS quadratic, and after solving for x: 1.29 < x <...

3 Answers · Science & Mathematics · 28/01/2018

9. ### How to solve the following expression algebraically: (x+y)^-2 = x^-2(1+y/x)^-2 Thanks.?

Your expression is an identity and not an equation LHS = (x + y)^-2 = 1/(x + y)^2 = 1/[ x(1 + y/x)]^2 = 1/x^2(1 + y/x)^2 = x^-2(1 + y/x)^-2 = RHS

1 Answers · Science & Mathematics · 17/01/2018

10. ### a,b>1 prove, a^2/(b-1)+b^2/(a-1)≥8?

...0; inequality becomes x(x + 1)² + y(y + 1)² ≥ 8xy; expand LHS: x³ + y³ + 2x² + 2y² + x + y = x³ + y³...

2 Answers · Science & Mathematics · 17/01/2018